A Cost-Effectiveness Analysis of Community Health Workers in Mozambique. (October 2015) - Bowser, Diana; Okunogbe, Adeyemi; Oliveras, Elizabeth; Subramanian, Laura; Morrill, Tyler
Introduction: Community health worker (CHW) programs are a key strategy for reducing mortality and morbidity. Despite this, there is a gap in the literature on the cost and cost-effectiveness of CHW programs, especially in developing countries.Methods: This study assessed the costs of a CHW program in Mozambique over the period 2010-2012. Incremental cost-effectiveness ratios, comparing the change in costs to the change in 3 output measures, as well as gains in efficiency were calculated over the periods 2010-2011 and 2010-2012. The results were reported both excluding and including salaries for CHWs.Results: The results of the study showed total costs of the CHW program increased from US1.34 million in 2010 to US1.67 million in 2012. The highest incremental cost-effectiveness ratio was for the cost per beneficiary covered including CHW salaries, estimated at US47.12 for 2010-2011. The smallest incremental cost-effectiveness ratio was for the cost per household visit not including CHW salaries, estimated at US0.09 for 2010-2012. Adding CHW salaries would not only have increased total program costs by 362% in 2012 but also led to the largest efficiency gains in program implementation; a 56% gain in cost per output in the long run as compared with the short run after including CHW salaries.Conclusions: Our findings can be used to inform future CHW program policy both in Mozambique and in other countries, as well as provide a set of incremental cost per output measures to be used in benchmarking to other CHW costing analyses.